Addressing the Challenges to Successfully Manage University-Industry R&D Collaborations - Fernandes, Gabriela (2022)
University-industry R&D collaborations (UICs) are becoming more critical for discovering innovations that can lead to the development of new products, services, and processes and, more broadly, social impact in terms of employment, economic development, and public health. The Covid-19 pandemic, for example, has seen an unprecedented rise in UICs and illustrates how vital their success can be for positively impacting the collaborators involved and society at large. Several challenges face the successful execution of UICs, not the least of which is the cultural difference between the collaborators. Overcoming these challenges is the subject of several research initiatives that seek to identify the critical success factors (CSFs) that UIC consortiums can use to develop their internal capabilities and project management maturity. The challenges facing one large UIC have been studied in Portugal. Practitioners and researchers were involved in generating insights into how the UIC could be more effective. This paper presents some of these challenges facing the UIC and how they were addressed. It also offers early results into the CSFs deemed essential by researchers and practitioners based on their experience together over seven years. Top CSFs include senior management commitment, effective communication, stakeholder engagement, good leadership, clear and realistic goals, mutual trust and respect, interpersonal teamwork, and clear roles and responsibilities.